Are aortic root and ascending aorta echocardiographic diameters by adult vs paediatric guidelines recommendations interchangeable?. (25th November 2020) - Servato, M.L; La Mura, L; Lopez Sainz, A; Granato, C; Teixido, G; Galian, L; Gutierrez, L; Gonzalez Alujas, M.T; Casas, G; Valente, F; Rodriguez Palomares, J.F; Evangelista, A
Abstract: Background: Both aortic root size and ascending aorta are clinical parameters with significant therapeutic implications which can be easily assessed by transthoracic echocardiography (TTE). However, measurement values may vary according to cardiac cycle and the edge convention used. Purpose: This study aimed to compare the aortic diameter values measured using the lastest recommendations of two different guidelines, adults and children, to determine the influence of these methods on echocardiographic measurements. Methods: Two hundred and fifty adult patients (56% male, 63±15 years of age) and 67 children (65% male, 10.04±4.5 years of age) in whom TTE was clinically indicated were included. Aortic diameters were measured twice at 2 levels (sinuses of Valsalva and ascending aorta): leading edge to leading edge during diastole, (L-L in D) following the 2015 American Society of Echocardiography (ASE) adults guidelines and inner edge to inner edge during systole (I-I in S) following the 2010 ASE paediatric guidelines. Results: Mean aortic diameters obtained by L-L in D and I-I in S are shown in Table 1. Correlation coefficient was 0.990 (CI95% 0.988–0.992) for sinuses of Valsalva measurements and 0.991 (CI95% 0.989–0.993) for ascending aorta in adult patients and 0.983 (CI95% 0.975–0.973) and 0.970 (CI95% 0.956–0.952) in childrens respectively. When both populations were analysed together, concordance correlation coefficients were 0.991 (CI95% 0.989–0.993) and 0.970 (CI95% 0.991–0.994), respectively. Bland- Altman analysis for each level measured (A: aortic root; B: ascending aorta) in the total cohort of 317 patients is shown in Figure 1. Mean aortic diameters and differences in the whole group are shown in Table 1. Conclusions: Measurement of aortic root and ascending aorta showed a significantly larger diameters by L-L in D than by I-I in S. However, these differences had subclinical significance and management implications. These similar diameter values may be used indifferently but systematically during follow-up. Systolic diameter expansion has a similar value to that of anterior aortic wall thickness; however, it is more vulnerable to changes in haemodynamic conditions. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Vall d'Hebron Research Institute